Two-Dimensional Forward-Backward Time-Stepping Approach for Tumor Detection in Dispersive Breast Tissues - Kismet, Hong Ping; Moriyama, Toshifumi; Takenaka, Takashi; Tanaka, Toshiyuki (2009)
The Forward-Backward Time-Stepping (FBTS) technique is applied to determine the presence and location of malignant tumor in the heterogeneous breast model. A new strategy is integrated in the FBTS algorithm to accurately estimate the dielectric properties of tissues. We demonstrate 2-D FBTS technique utilizing the numerical dispersive breast model in a free space. This new strategy manipulating Debye dispersion equation is proposed to treat dispersive case. Numerical simulation results show the FBTS algorithm has the potential to provide useful quantitative information of the breast’s internal composition.